Possible association between benign migratory glossitis and fissured tongue with psoriasis: A meta-analysis - Alberto Rodriguez-Archilla; Saliha El-Ouastani (Wolters Kluwer Medknow Publications, 2021)
Psoriasis is a chronic inflammatory dermatological disease that affects approximately 2% of the population. It is related to geographic tongue (GT) because both present similar clinical, histopathological, and genetic patterns, suggesting that GT could represent an oral manifestation of psoriasis. The objective of this study is to assess the possible relationship between psoriasis and its possible oral manifestations such as GT and/or fissured tongue (FT). A search for the articles on psoriasis and tongue or oral mucosa was performed in the next electronic databases: PubMed (MEDLINE and Cochrane Library), Web of Science, and Spanish Medical Index (SMI). From 175 potentially eligible articles, 151 were excluded for the several reasons: articles without full-text availability (119) and studies without clinical or usable data (32). Finally, 24 studies were included in this meta-analysis. The data were analyzed using the statistical software RevMan 5.4 (The Cochrane Collaboration, Oxford, UK). For dichotomous outcomes, the estimates of effects of an intervention were expressed as odds ratios (OR) with 95% confidence intervals. Among patients with psoriasis, 8.6% had a GT and 28.2% had a FT. Psoriasis patients were more likely to present both GT (OR: 3.61, P < 0.001) or FT (OR: 2.84, P < 0.001). Regarding the expression of histocompatibility antigens, patients with psoriasis and GT more frequently expressed type B13 and B57 antigens, whereas controls without psoriasis or GT showed more types B15, B17, B40, B58, C04, Cw6, DR5, and DRw6 antigens. Geographical tongue and FT are most often observed in patients with psoriasis.